Lipoprotein(a) and the effect of alirocumab on coronary and non-coronary revascularization following acute coronary syndrome. (3rd October 2022) - Steg, P; Szarek, M; Valgimigli, M; Islam, S; Zeiher, A M; Bhatt, D L; Bittner, V A; Diaz, R; Goodman, S G; Harrington, R A; Jukema, J W; Pordy, R; et al.
Abstract: Background: Many patients require arterial revascularization after an index ACS. Lipoprotein(a) is thought to play a pathogenic role in atherothrombosis. In the ODYSSEY OUTCOMES trial, the PCSK9 inhibitor alirocumab reduced major adverse cardiovascular events after ACS, with greater reduction among those with higher lipoprotein(a). Objectives: We determined whether the risk of first coronary or any (coronary, peripheral artery or carotid) revascularization after ACS was modified by the level of lipoprotein(a) and treatment with alirocumab or placebo. Methods: The ODYSSEY OUTCOMES trial (NCT01663402) compared alirocumab with placebo in 18, 924 patients with ACS and elevated atherogenic lipoproteins despite optimized statin treatment. Treatment effects were summarized by competing-risks proportional hazard models. Results: A total of 1559 (8.2%) patients had coronary, 204 (1.1%) peripheral artery, and 40 (0.2%) carotid revascularization after randomization. Alirocumab reduced first coronary revascularization (9.6% vs. 11.3% at 4 years; hazard ratio [HR] 0.88, 95% confidence interval [CI] 0.80–0.97; p=0.01) and any first revascularization (10.8% vs. 13.0%; HR 0.85, 95% CI 0.78–0.94; p=0.001). Baseline lipoprotein(a) quartile was directly associated with risk of coronary or any revascularization in the placebo arm (ptrend <0.0001) and inversely related to treatment HRs (ptrend <0.001). The greatest benefits of alirocumab on coronary or any revascularization were observed in patients with baseline lipoprotein(a) in the top quartile (≥59.6 mg/dL) (figures). Conclusions: Alirocumab reduced revascularization after ACS. The risk of revascularization and reduction in that risk with alirocumab were greatest in patients with elevated lipoprotein(a) at baseline. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): SanofiRegeneron Pharmaceuticals